2017
DOI: 10.1016/j.sjbs.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemical composition and antiedematogenic activity of the essential oil of Hyptis martiusii Benth

Abstract: Evaluations of the therapeutic potential of medicinal plants and their components have been the subject of many studies. Furthermore, the biological activities of various plant species have been reported in various pieces of literature. Benth (Lamiaceae), popularly known as "mad balm" is commonly found in the North, Southeast, and Northeast of Brazil. Its leaves are used ethnobiologically as antiulcerogenic, antimicrobial, antitumor and as insecticide. This study aimed to analyze the chemical composition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Shin et al [ 38 ] indicated that application of croton oil increased expression of COX-1 and COX-2 and increased PGE 2 production. These mechanisms increase vascular permeability, vasodilation and swelling due to the release of histamine and serotonin, which is followed by the synthesis of leukotrienes and prostaglandins [ 39 ]. Therefore, anti-inflammatory drugs such as aspirin that inhibit COX enzymes are effective in suppressing ear edema induced by croton oil [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al [ 38 ] indicated that application of croton oil increased expression of COX-1 and COX-2 and increased PGE 2 production. These mechanisms increase vascular permeability, vasodilation and swelling due to the release of histamine and serotonin, which is followed by the synthesis of leukotrienes and prostaglandins [ 39 ]. Therefore, anti-inflammatory drugs such as aspirin that inhibit COX enzymes are effective in suppressing ear edema induced by croton oil [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The essential oil of Medusantha martiusii (syn. Hyptis martiusii ), is composed predominantly by γ -3-carene ( 242 ) and 1,8-cineole ( 250 ) ( Caldas et al, 2014 ; Barbosa et al, 2017 ).…”
Section: Phytochemistrymentioning
confidence: 99%
“…In this context, in the Lamiaceae family, there are a plethora of species with rich content in essential oils, which are used in popular medicine as an alternative treatment for diseases [2] . For example, the genus Hyptis is considered of great economic importance since it is composed of triterpenes [3] , diterpenes [4] and sesquiterpenes [5] , that are responsible for interesting antimicrobial [ 6 , 7 ], insecticide [8] , analgesic [9] , [10] , [11] , and hypnotic-sedative and antipsychotic-like activity [12] .…”
Section: Introductionmentioning
confidence: 99%